Association of physical injury and mental health: Results from the National Comorbidity Survey- Adolescent Supplement - Jenness, Jessica L. (J Psychiatr Res, 2017)
Nonfatal injury is common among adolescents in the U.S., but little is known about the bi-directional associations between injury and mental health. Utilizing a nationally representative sample of U.S. adolescents, we examined 1) associations between lifetime mental health history and subsequent injury; 2) concurrent associations between injury and mental health; and 3) associations between injury and subsequent mental disorders. Data were drawn from the National Comorbidity Survey Replication-Adolescent Supplement (NCS-A), a national survey of adolescents aged 13 through 17 years (N=10,123). Twelve-month prevalence of nonfatal injury requiring medical attention was assessed along with lifetime, 12-month, and 30-day prevalence of DSM-IV depressive, anxiety, behavior, substance use, and bipolar disorders. We used Poisson regression to examine associations between 1) lifetime history of mental disorders and 12-month exposure to injury; 2) concurrent associations between 12-month exposure to injury and 12-month prevalence of mental disorders; and 3) 12-month exposure to injury and 30-day prevalence of mental disorders. A total of 11.6% of adolescents experienced an injury requiring medical attention in the year before the survey. Lifetime history of mental disorders was not associated with past-year injury. Behavior and bipolar disorders were concurrently associated with past-year injury. Past-year injury occurrence predicted increased risk for past-month anxiety disorders and decreased risk of past-month depressive disorders. Our findings reveal reciprocal associations between injury and mental disorders and highlight the need for systematic assessment, prevention, and treatment of mental disorders among injured youth.